Wordsworthian Chance - Burkett, Andrew (Romanticism and Victorianism on the Net, 2009)
AbstractFirst-generation Romantic poets generally hold a deeply rooted faith in the notion of the limitless nature of possibility, and in reaction to Enlightenment determinism, several of these poets strive for an understanding and representation of nature that is divorced from Enlightenment notions of causality. This essay specifically explores William Wordsworth’s poetic denunciation of such deterministic accounts of causality through an investigation of The Prelude’s (1799, 1805, 1850) complication of the assumption that the natural effect can be traced backward towards a single identifiable cause. I argue that in place of this principle of sufficient reason, Wordsworth embraces the notion of “chance” as possessing the inexhaustible powers of difference. In accordance with his fascination with the potentialities of the novel infinite, the idea of “chance” allows Wordsworth to challenge the notion of “necessity,” or the philosophic claim that steadfast and orderly laws determine all events in space and time. While Wordsworth certainly does not argue with the notion that cause-effect chains can be traced temporally back in time, such a genealogical record, he suggests, can only ever be deduced and constructed a posteriori. Only after the fact of its historical instantiation can the genealogical record of causal relations be deciphered and inscribed, he indicates. Such a genealogy, then, in no way undermines a faith in chance. Rather, according to Wordsworth, the record only makes the idea of chance all the more manifest. Such a posteriori inscriptions provide a distillation of the concept of chance. In this causal record Wordsworth locates the phantom outlines left in chance’s conceptual wake, or perhaps better stated, through the specters of the idea of chance.